Does aggressive local treatment have an impact on survival in children with metastatic rhabdomyosarcoma?. Issue 2 (January 2015) - Ben Arush, M.; Minard-Colin, V.; Mosseri, V.; Defachelles, A.S.; Bergeron, C.; Algret, N.; Fasola, S.; André, N.; Thebaud, E.; Corradini, N.; Bernier, V.; Martelli, H.; et al.
Abstract Purpose Due to the extensive initial distant tumour spread in metastatic rhabdomyosarcoma, the importance of local treatment is sometimes underestimated. A retrospective study was conducted to identify the prognostic value of aggressive local treatment in paediatric metastatic rhabdomyosarcoma. Patients Patients with metastatic rhabdomyosarcoma aged 1–21 years treated in France from 1998 to 2011 according to European protocols MMT-4-89, 4-91, 98 and recent national guidelines were selected. Survival comparison were performed between patients with 'aggressive local treatment' (surgery and radiotherapy) and exclusive surgery or radiotherapy, after exclusion of patients with early progression. End-points were event-free and overall survival (OS). Results A total of 101 children, median age 9 years, with majority of primaries in unfavourable sites (73 patients, pts), T2 tumours (66 pts), alveolar subtypes (65 pts) and large tumours (>5 cm, 83 pts) received various chemotherapy regimens. On univariate and multivariate analyses, OS was better after 'aggressive local treatment' (49 pts; 44.3 ± 8%), than after exclusive surgery (10 pts; 18.8% ± 15.5%) or exclusive radiotherapy (29 pts; 16.1 ± 7.2%, P < 0.006). Moreover, OS was better in the case of surgery with complete resection (41.1 ± 10.2%) or microscopic residue (56.4 ± 14.9%) than macroscopic residue (20.0 ± 12.6%; P < 0.03). Conclusions In this large retrospective analysis, OS appeared to be better for patients receiving 'aggressive local treatment' even after adjustment for the initial patient and tumour characteristics. Isolated debulking surgery is associated with a very poor outcome and should be avoided. Aggressive local treatment in patients with rhabdomyosarcoma, even with metastasis, should be seriously considered.